The dual lens of sustainability: economic and environmental insights into novel carbon reduction technologies using systems modeling, data science, and multi-objective optimization - Limb, Braden Jeffery, author; Quinn, Jason C., advisor; Simske, Steven J., advisor; Gallegos, Erika E., committee member; Ross, Matthew R. V., committee member (Colorado State University. Libraries, 2024)
In an era marked by escalating climate change and increasing energy demands, the pursuit of sustainable solutions in energy production and environmental management is more critical than ever. This dissertation delves into this challenge, focusing on innovative technologies aimed at reducing carbon emissions in key sectors: power generation, wastewater treatment, and aviation. The first segment of the dissertation explores the integration of thermal energy storage with natural gas power plants using carbon capture, a crucial advancement given the dominant role of fossil fuel-based power plants in electricity generation. Addressing the economic and operational drawbacks of current carbon capture and storage (CCS) technologies, this study evaluates various thermal storage configurations. It seeks to enhance plant performance through energy arbitrage, a novel approach to offset the large heat loads required for carbon capture solvent regeneration. By optimizing these technologies for current and future grid pricing and comparing their feasibility with other production methods, this research aims to strike a balance between maintaining reliable power generation and adhering to stringent environmental targets. Results show that resistively charged thermal storage can both increase CCS flexibility and power plant profits through energy arbitrage when compared to power plants with CCS but without thermal storage. Beyond electrical systems, addressing climate change also necessitates improving the energy efficiency of water treatment technologies. Therefore, the dissertation investigates the potential of nature-based solutions as sustainable alternatives to traditional water treatment methods in the second section. This section probes into the efficacy of green technologies, such as constructed wetlands, in reducing costs and emissions compared to conventional gray infrastructure. By quantifying the impact of these technologies across the U.S. and evaluating the role of carbon financing, the research highlights a pathway towards more environmentally friendly and economically viable water treatment processes. Results show that nature-based water treatment technologies can treat up to 37% of future nutrient loading while both decreasing water treatment costs and emissions compared to traditional water treatment techniques. The transportation sector will play a key role in addressing climate change as it is the largest contributor to greenhouse gas emissions. While most of the transportation sector is expected to transition to electric vehicles to decrease its carbon footprint, aviation remains hard to decarbonize as electric passenger aviation is expected to be range limited. Therefore, the final segment of the dissertation addresses the challenge of meeting the U.S. Department of Energy's Sustainable Aviation Fuel (SAF) goals. It involves a comprehensive analysis of various bioenergy feedstocks for SAF production, using GIS modeling to assess their economic and environmental impacts across diverse land types. The study employs multi-objective optimization to strategize the deployment of these feedstocks, considering factors like minimum fuel selling price, greenhouse gas emissions, and breakeven carbon price. Furthermore, agent-based modeling is used to identify policy incentives that could encourage farmer adoption of bioenergy crops, a critical step towards meeting the SAF Grand Challenge goals. This dissertation offers a comprehensive analysis of novel carbon reduction technologies, emphasizing both economic viability and environmental sustainability. By developing integrated models across key sectors affected by climate change, it explores the benefits and trade-offs of various sustainability strategies. Incorporating geospatial and temporal dimensions, the research uses multi-objective optimization and systems thinking to provide targeted investment strategies for the greatest impact. The results provide important insights and actionable plans for policymakers and industry leaders, contributing to a sustainable and low-carbon future in essential areas of the global economy.
Keywords: sustainability; systems modeling; waste water treatment; sustainable aviation fuels; life cycle assessment; techno-economics